Analysis of the Influence of Organizational Culture, Transformational Leadership Style and Employee Performance Assessment on Employee Satisfaction at Bio Farma - Prima Pratama Mulyawan; Narti Eka Putri (Jurnal Indonesia Sosial Teknologi, 2024)
Bio Farma (Persero) is a state-owned pharmaceutical company that was established in 1890 as a bacteriology laboratory by the colonial government of the Dutch East Indies and has undergone many transformations until it became Bio Farma (Persero) in 1997. This study aims to examine the influence of leadership style, organizational culture, and performance assessment on the satisfaction of permanent employees at Bio Farma. In this scientific paper, the influence of employee participation through latent variables Power Distance Index (FOC1), IDV (FOC2), Masculinity versus Femininity (FOC3), Uncertainty Avoidance Index (FOC4), Ideal Influence (FOC5), Individual Consideration (FOC6), Inspirational Motivation (FOC7), Intellectual Stimulation (FOC8), Validity (FOC9), Approval (FOC10), Reliability (FOC11), Objective (FOC12), Salary (FOC13), Promotion (FOC14), Co-workers (FOC15), Boss (FOC16), and Employment (FOC17). The researcher used Partial Least Square to see the influence between variables by testing the outer model as well as testing the inner model. Penelitian ini dilakukan terhadap 120 responden karyawan Bio Farma. The results of the study show that the three independent variables had a direct influence on employee satisfaction (p-value < 0.05), meanwhile, the simultaneous influence of the three variables showed no real influence (p-value = 0.639) with a p-value limit of < 0.5.